PENGARUH FEEL, THINK DAN ACT TERHADAP CITY BRANDING DAN IMPLIKASINYA TERHADAP KEPUTUSAN MENGUNJUNGI DESTINASI WISATA (Survei Terhadap Wisatawan Wisata Sejarah Di Kabup - Ajat Sudrajat (Eqien - Jurnal Ekonomi dan Bisnis, 2018)
In the competition against the number of tourist visits need to create a strong brand of a region, and found no cavities, avoid the aspect of vehicle congestion during the hours of work, clean environment conditions and neat and not chaotic city layout and the beauty of the city is always considered and resulted in the decline of tourists.The purpose of this research is to know how Feel, Think and Act, city branding and decision to visit historical tourism object with research method using descriptive veripikatif with path analysis technique, with respondent is domestic tourists with population 1580 and taken sample as much 286 people. The feel (X1) variables are on an agreed scale, think (X2) is on a very strong scale, act (X3), city branding (Y) and visiting decision (Z) are on the agreed scale. The relationship between the free variables of feel (X1), think (X2) and act (X3) shows the correlation of 0,544 (rx1x2), 0.642 (rx2x3) and 0.612 (rx1x3). The magnitude of the total influence of the independent variables: feel (X1), Think (X2) and Act (X3) on City Branding (Y) is expressed by the determinant coefficient (Ryx) 2 value of 34%. The magnitude of the total influence of the free variables: feel (X1), Think (X2) and Act (X3) on visiting decisions (Z) through City Branding (Y) is expressed by the coefficient of determination (Ryx) 2 of 70% outside model is 30%. Keywords: Feel, Think and Act, City Branding and Decision to visit